Modelling Self Purification of River Benue within Makurdi. - Aho, I. M.; Akpen , G. D.; Aniakor, C. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
This study considered biochemical oxygen demand (BOD), dissolved oxygen (DO), the re- oxygenation rate, the de-oxygenation rate, the self-purification rate model for River Benue within Makurdi reach. The hydrodynamic data were collected while re-oxygenation rate, de-oxygenation rate and self purification rate were calculated using DO and BOD at 14 different stations along the river stretch. An empirical model for self purification was generated analytically using multiple linear regression equation analysis. The pH varied from 6.8 to 8.08 while DO concentration between 4.0 mg/L and 6.3 mg/L; BOD concentration ranges from 1.0 mg/L to 2.0 mg/L; Mean re-oxygenation rate of 0.179 in the raining season and 0.1 in the dry season; Mean de-oxygenation rate of 0.1186 day-1 in the raining season and 0.1345 day-1in the dry season was calculated; Self purification coefficient had a mean value of 1.3398 in dry season and 0.8354 in rainy season;  The model has coefficient of determination (R2) and adjusted R2 of 0.5691 and 0.5469 respectively; a multiple correlation coefficient of 0.7544 and root mean squared error of 0.2433 between the observed field data and the model data. In conclusion, the river has good self purification ability and the model generated is reliable considering the root mean squared error.